Rapid quantification of free fatty acids in virgin coconut oil by FTIR spectroscopy - Marina, A.M.; Wan Rosli, W.I.; Noorhidayah, M. (Penerbit Universiti Kebangsaan Malaysia, 2015)
A rapid method for quantitative analysis of free fatty acids in virgin coconut oil (VCO) was determined using Fourier transform infrared (FTIR) spectroscopy. Thirty training samples of VCO were prepared by spiking lauric acid to VCO samples covering a range of 0.1% to 5% of free fatty acids. FTIR spectra between 1730 and 1690 cm-1 was used for quantitative determination of free fatty acids. A partial least square (PLS) model was calibrated to predict the free fatty acids content of VCO. A linear calibration curve was obtained for the actual value against FTIR predicted value which yields an equation of y = 0.9744x + 0.0006 and satisfactory results of root mean square error of prediction (RMSEP) of 0.1264 and correlation coefficient (R2) of 0.9281. Thus, FTIR spectroscopy with PLS regression can serve as important tools for determining the free fatty acids in VCO because it is rapid, accurate and environmental friendly compared to the conventional chemical analyses.